Way of Stress and Deformation Calculations in the Rails and Anchor Pins of Mining Rack-Railway Track - Frydrýšek Karel; Freis Jiří; Kolář Václav (Journal of Mechanical Engineering)
Article deals with the calculation issues of deflection and stress in the rail and pins, which are a part of the anchoring design for rack-railway tracks. The rack-railway track, is intended for the transport of excessively heavy loads and people inside mines. A longitudinal track dip can be up to ± 35deg. Practical application is focused on the calculations of pins and rails, for which a novel combination of analytical approaches and FEM is used, with dynamic loading and the theory of beams on an elastic foundation. The methodology is explained in details and the first results are listed. Everything stated in this article can be used to design transport systems not only in mining/underground constructions.